The C. elegans embryonic transcriptome with tissue, time, and alternative splicing resolution - Warner, Adam D.; Gevirtzman, Louis; Hillier, LaDeana W.; Ewing, Brent; Waterston, Robert H. (Genome Research, 2019)
We have used RNA-seq in Caenorhabditis elegans to produce transcription profiles for seven specific embryonic cell populations from gastrulation to the onset of terminal differentiation. The expression data for these seven cell populations, covering major cell lineages and tissues in the worm, reveal the complex and dynamic changes in gene expression, both spatially and temporally. Also, within genes, start sites and exon usage can be highly differential, producing transcripts that are specific to developmental periods or cell lineages. We have also found evidence of novel exons and introns, as well as differential usage of SL1 and SL2 splice leaders. By combining this data set with the modERN ChIP-seq resource, we are able to support and predict gene regulatory relationships. The detailed information on differences and similarities between gene expression in cell lineages and tissues should be of great value to the community and provides a framework for the investigation of expression in individual cells.
10.1101/gr.243394.118